Parenteral exposure to high HIV viremia leads to virus-specific T cell priming without evidence of infection. - Missale, G; Papagno, L; Penna, A; Pilli, M; Zerbini, A; Vitali, P; Pieroni, G; Urbani, S; Uggeri, J; Pinheiro, S; Rowland-Jones, S; Ferrari, C (2004)
Previous studies on CTL responses in HIV-exposed uninfected individuals assumed that the patients were exposed to replicating HIV, but the possibility that the immune responses detected were primed by exposure to a defective virus or viral antigen could not be excluded. Epidemiological and laboratory analysis of a nosocomial outbreak of acute hepatitis B unequivocally allowed the identification of an HIV-1- and HBV-co-infected patient with high plasma levels of both viruses, as the source case of the epidemics. This clinical setting provided a natural model for testing the HIV-specific T cell response in patients exposed to blood from a patient with highly replicating HIV. Parenteral exposure to both viruses led to acute hepatitis B in five subjects without evidence of HIV-1 infection. Cryopreserved lymphocytes derived from three exposed patients were tested ex vivo in an ELISPOT assay for IFN-gamma release upon stimulation with peptides from structural and non-structural HIV proteins; one of the patients was also tested with four HLA/class I tetramers. Circulating HIV-specific CD8 cells were detected by tetramer staining and a high frequency of T cells were able to release IFN-gamma upon stimulation with HIV peptides, showing in vivo T cell priming by HIV. These results unequivocally demonstrate a HIV-specific cell-mediated immune response in the absence of infection after exposure to highly replicating HIV.